Development of Oral Herbal Male Contraceptive - Akash Yadav; Shivangi Sharma; Shahid Nazir Wani; Kirti Kaushal; Priya Sharma (Current Aspects in Pharmaceutical Research and Development Vol. 8, 2022)
Background: Recognizing population management as a critical step toward global health encourages more research into male contraception. Despite the fact that there are numerous synthetic contraceptives on the market, they all have a variety of side effects. Different possible male contraceptive options, including hormonal, pharmacological, and immunological therapies, were studied over a lengthy period of time, and these methods demonstrated good antifertility effects with low failure rates when compared to condoms. Main Text: This chapter is focused on the idea of herbal contraceptives, which are an efficient way to restrict animal and human fertility. This review has focused on herbal medicinal plants and plant extracts that have been shown to have antifertility effects in males. The review considers plants that have been traditionally used for their spermicidal and antispermatogenic activities, as well as plants with reported animal studies and some with human studies for antifertility effects, as well as their doses, chemical constituents, and mechanism of action for the antifertility effect of the plants. The stages of sperm development, hormone production, and the mechanism of male contraceptives are also explained in this chapter. Conclusion: In terms of the current review’s relevance, it could be very valuable in producing plant monographs and suggestions for their use. Many of the plant species listed here could be useful as alternative oral fertility-regulating agents in males. As a result, more research into the chemical and biological features of these less-explored plants is needed to determine their contraceptive efficacy as well as to possibly identify their harmful effects, so that these substances can be used confidently to manage male fertility. In this field, new inventions are required to focus on modern, more potent drugs with less harmful content that are self-administerable, less expensive, and completely reversible.